Acute respiratory distress syndrome after cardiac surgery - Rong, Lisa Q.; Di Franco, Antonino; Gaudino, Mario (Journal of Thoracic Disease; Vol 8, No 10 (October 01, 2016): Journal of Thoracic Disease, 2016)
Acute respiratory distress syndrome (ARDS) is a leading cause of postoperative respiratory failure, with a mortality rate approaching 40% in the general population and 80% in the subset of patients undergoing cardiac surgery. The increased risk of ARDS in these patients has traditionally been associated with the use of cardiopulmonary bypass (CPB), the need for blood product transfusions, large volume shifts, mechanical ventilation and direct surgical insult. Indeed, the impact of ARDS in the cardiac population is substantial, affecting not only survival but also in-hospital length of stay and long-term physical and psychological morbidity. No patient undergoing cardiac surgery can be considered ARDS risk-free. Early identification of those at higher risk is crucial to warrant the adoption of sboth surgical and non-surgical specific preventative strategies. The present review focuses on epidemiology, risk assessment, pathophysiology, prevention and management of ARDS in the specific setting of patients undergoing cardiac surgery.